STRATEGI MEMBACA HURUF HIJAIYAH BAGI ANAK BERKEBUTUHAN KHUSUS DI RA AL-WASHLIYAH BANDAR DURIAN - Pasaribu, Siti Jariah (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
Based on field experiences, the use of learning methods, especially reading strategies for hijaiyah letters for children with special needs, still relies on conventional methods and students face difficulties in receiving the lessons. The insufficient number of educators and the fact that their educational background is not from Special Education also become obstacles in the learning process. This research aims to understand the methods teachers use in teaching hijaiyah letters to children with special needs. This type of research is qualitative field research. The data collection techniques used are observation, interviews, and documentation. The results of this study show that the method used by teachers in teaching hijaiyah letters to hearing-impaired students employs the iqro’ method with individual strategies and the use of oral and sign language approaches. The use of this method has a fairly high effectiveness when applied to reading Hijaiyah letters for children with special needs.